2001
DOI: 10.1177/0021886301372001
|View full text |Cite
|
Sign up to set email alerts
|

The Unexpected Effects of a Sexual Harassment Educational Program

Abstract: This study evaluated a sexual harassment program for staff and faculty employees at a metropolitan university. One hundred men and 97 women who participated in the program and 141 men and 178 women who did not participate responded to a self-report questionnaire through campus mail. Analysis of variance was used to test for effects of program participation and employee gender on five outcome variables. Results indicated that participants showed more knowledge about sexual harassment than did nonparticipants an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 38 publications
2
81
0
1
Order By: Relevance
“…Moreover, recipients of training are less likely to blame victims or trivialize sexual harassment (Lonsway et al 2008 ;Magley et al 2004 ). Bingham and Scherer ( 2001 ) found that individuals who had sexual harassment training had greater beliefs that sexual behavior is inappropriate in the workplace. However, Perry and colleagues ( 1998 ) found that these attitudinal changes were only short-term, failing to persist over time.…”
Section: Sexual Harassment Training Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, recipients of training are less likely to blame victims or trivialize sexual harassment (Lonsway et al 2008 ;Magley et al 2004 ). Bingham and Scherer ( 2001 ) found that individuals who had sexual harassment training had greater beliefs that sexual behavior is inappropriate in the workplace. However, Perry and colleagues ( 1998 ) found that these attitudinal changes were only short-term, failing to persist over time.…”
Section: Sexual Harassment Training Programsmentioning
confidence: 99%
“…Other researchers fi nd that, after sexual harassment training, individuals (especially men) report increased knowledge of organizational policies and behaviors that constitute sexual harassment (Antecol and Cobb-Clark 2003 ;Bingham and Scherer 2001 ). Sexual harassment training is also associated with greater satisfaction with the organization's harassment policies or reporting procedures (Magley et al 2004 ;Reese and Lindenberg 1997 ).…”
Section: Sexual Harassment Training Programsmentioning
confidence: 99%
“…The fact that reactions were infrequently discussed as a means to evaluate sexual harassment training is an encouraging finding because measuring reactions, while an easy strategy for training evaluation, does not provide direct information about learning (Bingham & Scherer, 2001;Kirkpatrick, 1996). Unfortunately, the effect of training on behaviors was also discussed quite infrequently.…”
Section: Training Evaluationmentioning
confidence: 99%
“…Fitzgerald and Shullman (1993) described the lack of attention to the evaluation of sexual harassment interventions as a "glaring omission" (p. 16) in the sexual harassment literature. Reviewing the literature eight years later, Bingham and Scherer (2001) identified only nine published reports that systematically evaluated a sexual harassment training program in a workplace or educational setting.While there is little research on the effectiveness of sexual harassment training, there has been an explosion in general trainingrelated research in the past 10 years (Salas & Cannon-Bowers, 2001). In their review of the training research literature, Salas and CannonBowers (2001) noted that "the field can now offer sound, pedagogically based principles and guidelines to practitioners and instructional developers" (p. 473).…”
mentioning
confidence: 99%
“…Frank Dobbin and Alexandra Kalev's (2016) work on corporate implementation of various affirmative action and diversity programs shows that diversity training may actually result in less integration and more grievances filed. Likewise, recent research (Edelman and Galanter 2014;Bingham and Scherer 2001) notes that sexual harassment training may result in more sexual harassment. Programs aimed at educating workers about compliance with formal policies are not effective.…”
Section: For Corporate Decision Makersmentioning
confidence: 99%